2021
DOI: 10.3389/fcell.2021.791335
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell RNA Sequencing Revealed the Heterogeneity of Gonadal Primordial Germ Cells in Zebra Finch (Taeniopygia guttata)

Abstract: Primordial germ cells (PGCs) are undifferentiated gametes with heterogeneity, an evolutionarily conserved characteristic across various organisms. Although dynamic selection at the level of early germ cell populations is an important biological feature linked to fertility, the heterogeneity of PGCs in avian species has not been characterized. In this study, we sought to evaluate PGC heterogeneity in zebra finch using a single-cell RNA sequencing (scRNA-seq) approach. Using scRNA-seq of embryonic gonadal cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 47 publications
1
18
0
Order By: Relevance
“…We obtained gene expression signatures for eight types of gonadal cells in both species. Although our research group has previously identified nine types of gonadal cells in zebra finch, 19 some of the clusters assigned to supporting cells are shared with clusters assigned to steroidogenic cells. Steroidogenic lineages may be derived from supporting cells of the chicken embryonic gonad, as evidenced by the detection of cells expressing both supporting and steroidogenic cell markers among chicken gonadal cells 25 .…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…We obtained gene expression signatures for eight types of gonadal cells in both species. Although our research group has previously identified nine types of gonadal cells in zebra finch, 19 some of the clusters assigned to supporting cells are shared with clusters assigned to steroidogenic cells. Steroidogenic lineages may be derived from supporting cells of the chicken embryonic gonad, as evidenced by the detection of cells expressing both supporting and steroidogenic cell markers among chicken gonadal cells 25 .…”
Section: Discussionmentioning
confidence: 82%
“…We newly generated 10× single‐cell transcriptome data for chicken embryonic gonads for the identification of major cell types. These data were combined with our previously reported zebra finch data 19 to investigate differences in signaling pathways (Figure 1A). After quality control, 12 611 and 10 778 cells were sequenced from pooled male and female gonads ( n = 6 each), respectively (Figure 1B and Figure S1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations